2020
DOI: 10.2105/ajph.2020.305659
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Access to Abortion Among Women in the United States in 2018: Variation by State Abortion Policy Context

Abstract: Objectives. To describe perceptions of access to abortion among women of reproductive age and their associations with state abortion policy contexts. Methods. We used data from the 2018 Survey of Family Planning and Women’s Lives, a probability-based sample of 2115 adult women aged 18 to 44 years in US households. Results. We found that 27.6% of women (95% confidence interval [CI] = 23.3%, 32.7%) believed that access to medical abortion was difficult and 30.1% of women (95% CI = 25.6%, 35.1%) believed that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…However, past research has demonstrated that search results and access to information are not equivalent for people in different areas of the US [ 11 ]. Prior findings highlight that while search results hindering abortion access are a concern across the US, people who face more barriers to abortion access likely also face additional barriers to finding reliable information online [ 3 ]. This is of greater concern when considering that users who face barriers to accessing in-person healthcare services are more likely to turn to the internet for health information than people who do not face the same barriers [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, past research has demonstrated that search results and access to information are not equivalent for people in different areas of the US [ 11 ]. Prior findings highlight that while search results hindering abortion access are a concern across the US, people who face more barriers to abortion access likely also face additional barriers to finding reliable information online [ 3 ]. This is of greater concern when considering that users who face barriers to accessing in-person healthcare services are more likely to turn to the internet for health information than people who do not face the same barriers [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…2 Page was excluded from quality assessment as the only educational/information content it contained was within a video. 3 Page was excluded from analysis as it was a news article, not providing educational/information content. https://doi.org/10.1371/journal.pone.0240664.t002 Health education page 0 (-) 0 (-) 0 (-) 4 (36.4%) 4 (19.0%) 1 Page rank out of pages presenting educational/information content to users, excluding pages on YouTube and news articles, and pages presenting a sub-page of a page already assessed.…”
Section: Top Page Ranking Top Page Urlmentioning
confidence: 99%
See 1 more Smart Citation
“…Social development promotes women's empowerment, gender equality, health, and women's rights (Bulatao & Ross, 2003;DeJong, 2006;DeJong, Bahubaishi, & Attal, 2012;McGuire, 2010;Shen & Williamson, 1999). In this regard, abortion rights, which is a significant aspect of woman's right (Center for Reproductive Rights, 2011;Committee on Economic, Social and Cultural Rights, 2000;Wild & Kunst, 1995), is of high importance as it is one of the most contested political issues in the recent times (Norrander & Wilcox, 2001;Perreira, Johnston, Shartzer, & Yin, 2020). Lack of literature on the impact of social development factors on abortion rights is a significant limitation in the theoretical conceptualization of abortion rights.…”
Section: Introductionmentioning
confidence: 99%